(untitled) (REMUNOM, 2023)
The importance of Information Technology in institutions, particularly computers and other IT equipment, is now irrefutable. Day after day this equipment becomes obsolete or damaged. This research aimed to encourage through its benefits the use of green IT in public institutions in Mozambique, and to this end it presents as a proposal ecologically correct policies to reduce the problems arising from the poor management of electronic waste in public institutions. Such policies deal with the processes of scrapping and reuse of computer equipment in order to contribute to environmental sustainability. Being this work of Applied Nature. This research is a field study, and for data collection the authors made use of the following data collection instruments: Interview, Direct Observation (photographic records), and the Bibliographic Method (which basically consisted of the collection and analysis of bibliographic sources that address green IT, as well as the benefits that can come from the adoption of practices and policies considered green in conventional IT installations). The research has a qualitative approach, where the authors studied the e-waste phenomenon without focusing on the number of obsolete equipment, but only on how they are treated, stored or reused after the end of their useful life. It should be noted that it is exploratory, where the authors explored as much as possible the issues related to the e-waste problem, and the factors that foster the growth of this problem that constitutes a risk to human and environmental health in institutions. The results show that institutions do not follow green IT practices in IT asset management. Keywords: Green IT; Sustainability; Electronic Waste; Reuse.